Proceedings of the 2017 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2017
DOI: 10.1145/3027063.3053119
|View full text |Cite
|
Sign up to set email alerts
|

"Like" it or not

Abstract: The "like" button on many social media platforms allows individuals to express endorsement of content. However, sites with a "liking" feature, such as Facebook, also permit users to edit or change the content of the original post after it has been published and "liked" by other users. This can be problematic if a transparent edit history is not (easily) available. In this paper, we report an online survey that assessed how individuals interpret what has changed in such a case. We tested four interface designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although beginning to acknowledge liking as an increasingly popular social function (Jin, Wang, Luo, Yu, & Han, 2011) some studies refer to Likes as "non-text feedback" (Burke, Marlow, & Lento, 2009) and "lightweight interaction" (Backstrom, Kleinberg, Lee, Danescu-Niculescu-Mizil, & Max, 2013;Burke, Kraut, & Marlow, 2011). Jang and colleagues refer to Likes, Favorites (on Twitter) and Re-pinning (on Pinterest) as "micro expressions" (Jang, Han, Shih, & Lee, 2015) and Meixner and Marlow describe Likes as "endorsement of content" (Meixner & Marlow, 2017). Taking a slightly different approach and exploring the social value of Likes, some studies have concluded that Likes can serve as tokens of emotional gratification and support.…”
Section: Social Media Skillsmentioning
confidence: 99%
“…Although beginning to acknowledge liking as an increasingly popular social function (Jin, Wang, Luo, Yu, & Han, 2011) some studies refer to Likes as "non-text feedback" (Burke, Marlow, & Lento, 2009) and "lightweight interaction" (Backstrom, Kleinberg, Lee, Danescu-Niculescu-Mizil, & Max, 2013;Burke, Kraut, & Marlow, 2011). Jang and colleagues refer to Likes, Favorites (on Twitter) and Re-pinning (on Pinterest) as "micro expressions" (Jang, Han, Shih, & Lee, 2015) and Meixner and Marlow describe Likes as "endorsement of content" (Meixner & Marlow, 2017). Taking a slightly different approach and exploring the social value of Likes, some studies have concluded that Likes can serve as tokens of emotional gratification and support.…”
Section: Social Media Skillsmentioning
confidence: 99%